Pathophysiologic features of Takotsubo Cardiomyopathy: A review of the literature (Ibrahim Cardiac Medical Journal, 2015)
Takotsubo cardiomyopathy is a newly recognized cause of chest pain mimicking a myocardial infarction in post-menopausal women. It is diagnosed based on clinical criteria established at the Mayo Clinic and imaging studies, including echocardiography, cardiac MRI, angiography, and left ventriculography. Several hypotheses have been postulated towards its etiology, with the dominant theory being cathecholamine toxicity to the myocardium in response to a stressful trigger. Pathologic investigations are limited, based mostly on autopsy findings, and represent inflammatory and fibrotic replacement of the myocardium. Here, we will address the current understanding of the disease entity of Takotsubo cardiomyopathy, its clinical mimics, and its pathophysiology.Ibrahim Cardiac Med J 2013; 3(1&2): 39-48